A KNOTTED1-LIKE HOMEOBOX Protein Regulates Abscission in Tomato by Modulating the Auxin Pathway - Ma, Chao (Plant Physiol, 2015)
A gene encoding a KNOTTED1-LIKE HOMEOBOX PROTEIN1 (KD1) is highly expressed in both leaf and flower abscission zones. Reducing the abundance of transcripts of this gene in tomato (Solanum lycopersicum) by both virus-induced gene silencing and stable transformation with a silencing construct driven by an abscission-specific promoter resulted in a striking retardation of pedicel and petiole abscission. In contrast, Petroselinum, a semidominant KD1 mutant, showed accelerated pedicel and petiole abscission. Complementary DNA microarray and quantitative reverse transcription-polymerase chain reaction analysis indicated that regulation of abscission by KD1 was associated with changed abundance of genes related to auxin transporters and signaling components. Measurement of auxin content and activity of a DR5::β-glucuronidase auxin reporter assay showed that changes in KD1 expression modulated the auxin concentration and response gradient in the abscission zone.